Exploring the occurrence of the Impostor Phenomenon and level of self-efficacy amongst students in university courses dominated by the opposite gender - Maree, David J.F. (University of Pretoria, 2021)
Mini Dissertation (MA (Research Psychology))--University of Pretoria, 2020.